Managing the Not-Yet: The Architectural Project Under Semiocapitalism. Issue 2 (4th May 2017) - Runting, Helen; Torisson, Fredrik
Abstract: Under conditions of semiocapitalism – wherein signs, rather than goods or even services, are the main output of abstract production – the architectural "project" has become the primary technology for organizing architectural labor. The project, we argue, also acts as a capture device capable of linking economic production and the production of subjectivity, facilitating both the reproduction of (architectural) labor, on the one hand, and the financing of schemes, on the other. Both outcomes, we posit, are dependent on the production of anticipatory affects that imbue legitimacy by citing the past and factoring in the future.